SOCIAL APPROACH OF THE RELATIONSHIP CONCEPT IN INTERNATIONAL RELATIONS - TUDOR, Salanțiu (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
In this paper, we will address to deficits of the study of relationship construction in IR by approaching the meaning of the concept in network structures. After presenting the interactions patterns as one of links sources as well as of conceptualizing of relationship, we will introduce the social roles of relations as an approach of the social processes. We will show that relationship have a relative character that is related with information flow, culture interaction and which is detached from the realism perspective. Furthermore, the approach will offer a theoretical surveillance from social and group’s perspective of the interconnectivity between international actors.